Aarskog-Scott Syndrome: Clinico-Radiological Illustration of a Rare Case - Akanksha Gupta; Ravi Prakash Sasankoti Mohan; Sumit Goel; Swati Gupta (Global Journal of Rare Diseases - Peertechz Publications, 2016)
Aarskog-Scott Syndrome is a rare syndrome and is estimated to occur in 1 in 1 million individuals in general population. It is transmitted in an X-linked recessive manner and occurs due to FGD1 gene mutation. It has facial, genital and digital hands symptoms, musculoskeletal anomalies and affected growth. Here we present a case of Aarskog-Scott syndrome in an 18-year-old male patient with the chief complaint of irregularly placed teeth. In addition to all the classical features, presence of talon cusp was an interesting intraoral finding which has never been reported previously in dental literature.